Study on the factors affecting root initiation and survival rate of plants obtained by ovary culture of Brassica campestris× B. oleracea - ZHANG Guo-qing; GU Hong-hui; XU Ling; HE Yun; ZHOU Wei-jun (浙江大学学报. 农业与生命科学版)
Using the regenerated plants obtained from interspecific crosses between Brassica campestris and B. oleracea through ovary culture techniques, the experiment was conducted to examine the factors affecting root initiation and survival rate of these regenerated plants. Of the media studied, the best response was observed from the MS media supplemented with 1.0 mg/LBA+0.1 mg/L NAA. Among three cross combinations, the regenerated plants from the cross between B. campestris × B. oleracea(715 × 6012) showed the best result, with the number of roots and length of roots reaching 9.51 and 4.7 cm, respectively. Of the culture durations studied, better response was obtained from the regenerated plants cultured for 14 days than for 7 days. However, there was no obvious difference of the number of roots and length of roots, when the regenerated plants cultured for over 14 days. The result also showed no significant difference of the leaf number and the width of maximum leaf between various genotypes and culture durations. The regenerated plants from three cross combinations were hardened for 8 days and their survival rate reached over 80%, which was obviously better than those hardened for 4 days.